Game-based learning in engineering education: Using the Goldratt Simulator to learn about the theory of constraints - Hotta, Bárbara Yumi; Machado, Bruna Andrade; Souza, Fernando Bernardi de; Lima, Pedro Augusto Bertucci; Alves, Anabela Carvalho (Revista Gestão da Produção Operações e Sistemas, 2024)
Paper aims - This study evaluated the application of the Goldratt Simulator as a supporting tool in a Theory of Constraints (TOC) course. Moreover, this research developed an evaluation instrument to analyze the learning outcomes of the game-based learning. Originality - The game-based learning literature lacks analysis of approaches to teach topics related to the TOC. Research method - This research employed an action-research method consisting of the planning, action and evaluation phases. The study was conducted in a Production Engineering undergraduate program in Brazil Main findings - Students who took the game reported that classes were more interesting. Some students opted not to play the game, which presents the challenge of planning learning activities suitable for different students’ profiles. The combination of the game with the evaluation instrument highlighted doubts that students presented regarding concepts previously taught by the professor. Implication for theory and practice - Game-based learning is a promising approach in higher education; yet, some students declined participating in the activities. Students who participated, however, declared enjoyment in the activity and suitability of The Goldratt Simulator to learn about TOC. These results shed light on the necessity of striking a balance between traditional and new educational approaches.